Short-term exposure to air pollutants increases the risk of hospital admissions in patients with Parkinson's disease – A multicentric study on 18 French areas. (1st November 2021) - Goria, Sarah; Pascal, Mathilde; Corso, Magali; Le Tertre, Alain
Abstract: Background: Recent studies have investigated the potential neurological impacts of short-term exposure to air pollutants, but with limited evidence. Objective: To analyze the relationship and quantify the short-term association of air pollution (PM10, PM2.5, NO2 and ozone) and hospital admissions for Parkinson's disease (PD), in 18 French areas. Methods: We modeled the daily number of PD-related hospital admissions in each area using a generalized additive Poisson regression model for the 2009–2017 period, introducing air pollutants as the main environmental variable and daily temperature as covariate. We controlled for long-term trend and seasonality. Results: A small but significant influence of PM10, PM2.5 and NO2 on all-ages PD hospital admissions was observed, of a similar order of magnitude (1.010 [95% CI: 1.004; 1.016], 1.010 [1.003; 1.017], and 1.011 [1.005; 1.016] for a 10 μg/m 3 increase in PM10, PM2.5 and NO2, respectively). We also found an increase in hospitalization risks, at the limit of significance, associated with ozone (1.001 [95% CI: 0.999; 1.004]). Conclusion: Our results suggest a short-term association between PM, NO2, ozone and daily hospital admissions due to PD. Highlight: Air pollution may exacerbate symptoms of Parkinson's disease (PD). Air pollution increases the risk of hospital admissions for PD in France. This effect is stronger during spring and summer. Improving air quality could improve the quality of life of PD patients.